The photovoltaic revolution is on: How it will change the electricity system in a lasting way. (15th February 2023) - Haas, Reinhard; Duic, Neven; Auer, Hans; Ajanovic, Amela; Ramsebner, Jasmine; Knapek, Jaroslav; Zwickl-Bernhard, Sebastian
Abstract: Electricity generation from photovoltaic (PV) plants plays a major role in the decarbonization of the energy sector. The core objective of this paper is to identify the most important conditions for the future development of PV in order to achieve its greatest possible benefits of PV systems for society. This analysis is based on the documentation of the historical deployment of quantities of PV and on the lessons learned regarding cost developments. In addition, the improvements of PVs technical and environmental performance parameters are investigated. A major result is that the impact of PV feed-in on network capacities may be substantial. Hence, classical energy-based network charges are inadequate. Changes in tariff and pricing structures are needed especially on retail level. The major conclusions is that customers should also receive time-variable price signals that tells them the real-time value of electricity in the system and provides incentives for taking electricity from the grid or feed-in. In addition, the tariffs should have components for maximum power from and to the grid. Another conclusion is that on retail level grid parity already today provides sufficient incentives to purchase a PV system in many countries without additional financial support. Highlights: The 4 major Highlights of this paper are: Grid parity has made PV systems economically attractive already in many countries. Grid parity has reduced the need for subsidies for small decentralized systems. Retail pricing systems providing fair conditions for all customers are needed. Final customers tariffs should include components for power from and to the grid.